utocriticism of the Musyarakah Contract Fatwa Application in Islamic Financial Institutions - arfian risqi mubarok (ITB AAS INDONESIA Surakarta, 2022)
In line with the times, the economic system also experienced development. Islamic financial institutions (LKS) emerged as an alternative to the decline of the conventional economic system. Islamic banking is required to always improve services and develop products that are competitive and can meet the needs of the community. However, the facts show that the development of products and services to meet people's demands for Islamic banking transactions has not been running optimally, especially in partnership-based products. Fatwa of the National Sharia Council Number 08/DSN-MUI/IV/2000, states that community needs to improve welfare and business sometimes require funds from other parties, including through musyarakah financing. However, in the implementation of this musharaka contract, especially in Islamic banking, banks do not seem to have implemented the contract as a whole. This can be seen when banks provide financing to customers who apply for funds based on syirkah or musyarakah contracts to carry out business projects. banking does not seem to have an important role in monitoring and evaluation to manage the business project.